Sodium tanshinone IIA sulfonate protects ARPE-19 cells against oxidative stress by inhibiting autophagy and apoptosis. Issue 1 (December 2018) - Han, Dongmei; Wu, Xingwei; Liu, Libin; Shu, Wanting; Huang, Zhenping
Abstract Oxidative stress in retinal pigment epithelium (RPE) is considered to be a major contributor to the development and progression of age-related macular degeneration (AMD). Previous investigations have shown that sodium tanshinone IIA sulfonate (STS) can alleviate oxidative stress in haemorrhagic shock-induced organ damage and cigarette smoke-induced chronic obstructive pulmonary disease in mice. However, whether STS has a protective effect in ARPE-19 cells under oxidative stress and its exact mechanisms have not yet been fully elucidated. In the present study, we utilized H2 O2 to establish an oxidative stress environment. Our findings show that STS activated the PI3K/AKT/mTOR pathway to inhibit autophagy and diminished the expression of the autophagic proteins Beclin 1, ATG3, ATG7 and ATG9 in ARPE-19 cells under oxidative stress. Detection of the intrinsic apoptosis-related factors BAX, mitochondrial membrane potential (MMP), caspase-9, caspase-3 and BCL-2, as well as the extrinsic apoptosis-related factors c-FLIP, v-FLIP and caspase-8, confirmed that STS inhibited the intrinsic and extrinsic apoptotic pathways, and attenuated apoptosis in ARPE-19 cells under oxidative stress conditions. These findings shed new light on the protective effects of STS in ARPE-19 cells and its mechanisms under oxidative stress to provide novel and promising therapeutic strategies for AMD.